Anticancer Effects and Mechanisms of OSW-1 Isolated From Ornithogalum saundersiae: A Review - Zhan, Zhixin; Liu, Ziqiang; Lai, Jiacheng; Zhang, Chaochao; Chen, Yong; Huang, Haiyan (Frontiers in Oncology, 2021)
For centuries, cancer has been a lingering dark cloud floating on people's heads. With rapid population growth and aging worldwide, cancer incidence and mortality are growing rapidly. Despite major advances in oncotherapy including surgery, radiation and chemical therapy, as well as immunotherapy and targeted therapy, cancer is expected be the leading cause of premature death in this century. Nowadays, natural compounds with potential anticancer effects have become an indispensable natural treasure for discovering clinically useful agents and made remarkable achievements in cancer chemotherapy. In this regards, OSW-1, which was isolated from the bulbs of Ornithogalum saundersiae in 1992, has exhibited powerful anticancer activities in various cancers. However, after almost three decades, OSW-1 is still far from becoming a real anticancer agent for its anticancer mechanisms remain unclear. Therefore, in this review we summarize the available evidence on the anticancer effects and mechanisms of OSW-1 in vitro and in vivo, and some insights for researchers who are interested in OSW-1 as a potential anticancer drug. We conclude that OSW-1 is a potential candidate for anticancer drugs and deserves further study.